2015
DOI: 10.1021/acs.jpcc.5b11000
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electromagnetic Absorbing Properties of Titanium Carbonitride with Quantificational Carbon Doping

Abstract: Recent studies to explore the enhanced electromagnetic properties of TiN and TiC reported that TiNC has a good performance in EM wave absorption. We prepared TiNC with quantificational percentages of carbon doping in this work. Nanotitanium oxide precursor was prepared via sol–gel method, then submicron TiN(1–x)C x with different carbon content (x = 0, 0.2, 0.4, 0.6, 0.8) was obtained via solid–gas reaction by nitriding at 900 °C with nitrogen and carbon doping at 1700 °C with argon. The composition and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…It is known that good impedance matching which requires the balance between permittivity and permeability is the prerequisite for EM wave entering absorber. The impedance matching degree ∆ of the FeSiAl-8 and FeSiAl/MWCNTs can be calculated in the following equations 45 46 :…”
Section: Resultsmentioning
confidence: 99%
“…It is known that good impedance matching which requires the balance between permittivity and permeability is the prerequisite for EM wave entering absorber. The impedance matching degree ∆ of the FeSiAl-8 and FeSiAl/MWCNTs can be calculated in the following equations 45 46 :…”
Section: Resultsmentioning
confidence: 99%
“…The second term describes the conduction current and resultant conduction loss under the incidence of EM wave. This kind of current would transform the incident EM energy into other forms of energies and such process would take place at all frequencies . It has been known that three kinds of polarization mechanisms could contribute to the dielectric loss of the filler phase in the measured frequency range: 1) electronic polarization that generally produces dielectric loss at ultrahigh frequencies; 2) ionic polarization because of the introduction of Nb 5+ ions, which possess a higher valence state and easier to move inside the lattice under external electric field; and 3) conduction polarization due to the existence of oxygen vacancies, which originates from the mismatch between the ionic radius of Nb 5+ and Fe 3+ in the lattice .…”
Section: Resultsmentioning
confidence: 99%
“…65 Hong et al investigated microwave absorption properties of titanium carbonitride and found that thin microwave absorbers can be realized by optimal doping of carbon in the compound. 66 Silica-nickel-carbon composites are also reported to have good absorption characteristics. 67 A metasurface containing graphene patches as shown in Fig.…”
Section: Microwave Absorbersmentioning
confidence: 99%
“…Table IV gives a clear picture of different microwave-absorbing materials that have been discussed in this paper and their absorption characteristics. 64 8.2-18 2.5 Titanium carbonitride (TiN 0:2 C 0:8 ) 66 11.1-13.6 1.32 40 wt.% Silica-Ni-C composite Shelly hollow microspheres 67 5.7-18 2.4-4 2 wt.% CNT/rice husk ash composite 127 12.48-16.47 2 40 wt.% Rice husk/nontoxic glue binder 139 6.3-7.1 37.5 ( # pyrolysis temperature, *À20 dB absorption frequency bandwidth).…”
Section: Other Important Materialsmentioning
confidence: 99%